The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ece3.9144
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of variation in early‐life telomere length in a bird metapopulation

Abstract: Environmental conditions during early‐life development can have lasting effects shaping individual heterogeneity in fitness and fitness‐related traits. The length of telomeres, the DNA sequences protecting chromosome ends, may be affected by early‐life conditions, and telomere length (TL) has been associated with individual performance within some wild animal populations. Thus, knowledge of the mechanisms that generate variation in TL, and the relationship between TL and fitness, is important in understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 228 publications
0
26
1
Order By: Relevance
“…We have previously found no associations between nestling TL and survival in these sparrow populations, which showed high (presumably extrinsic) juvenile mortality 50 . Effects of selective disappearance of individuals with short TL and/or higher telomere shortening rates could therefore be masked by the majority of individuals having only one early-life TL measurement.…”
Section: Methodsmentioning
confidence: 69%
See 3 more Smart Citations
“…We have previously found no associations between nestling TL and survival in these sparrow populations, which showed high (presumably extrinsic) juvenile mortality 50 . Effects of selective disappearance of individuals with short TL and/or higher telomere shortening rates could therefore be masked by the majority of individuals having only one early-life TL measurement.…”
Section: Methodsmentioning
confidence: 69%
“…2). This suggests that the negative effects of growth 48 , environmental stressors 50 and inbreeding 86 on early-life TL previously described in these populations may have lasting effects on TL later in life 19,84 . Recent studies have found a positive genetic correlation close to 1 between TL measurements within individuals, suggesting that the same genes are involved in controlling TL at different ages 32,42,47 .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The study populations were included in a longterm study (e.g. Jensen et al, 2013;Kvalnes et al, 2017;Le Pepke et al, 2021;Pepke et al, 2021;Ringsby et al, 1820;Rønning et al, 2016;Stubberud et al, 2017), where a large proportion of birds (>85%) were captured annually at Leka and Vega during winters 2002-2015(Vega until 2014 and since 2012 at Lauvøya (Kvalnes et al, 2017). They have a known history of different selection regimes, as Leka and Vega were subjected to an artificial selection experiment (on tarsus length) during 2002-2005(Kvalnes et al, 2017Pepke et al, 2021;Ringsby et al, 1820).…”
Section: Introductionmentioning
confidence: 99%